BORDER LOCATION AND LOCAL ECONOMY ON THE EXAMPLE OF SELECTED MUNICIPALITIES OF THE LUBUSKIE VOIVODESHIP (Research Bulletins of the Faculty of Economic Sciences, 2024)
The aim of the research was to present the impact of the border location of local government units on their local economy. The example of three communes located in the Lubusz Voivodeship was used: two urban communes: Gubin and Kostrzyn nad Odrą, and the urban-rural commune of Słubice. In terms of research methods, case studies of selected investment projects were used. Based on data from 2017-2023, selected investments in selected municipalities implemented in cross-border cooperation were analyzed. The analyzes conducted show that the border location does not have a positive impact on the local economy of the surveyed communes. A border location offers many benefits to municipalities. It enables faster local development, helps to improve the activities of municipal authorities by exchanging experiences with partners from abroad, and encourages local entrepreneurs to establish cooperation with entrepreneurs operating on the other side of the border.
Keywords: border location, budget management, commune, Lubuskie Voivodeship